The effects of new AAOIFI standards on Sukuk in choosing the most authentic Islamic principles - Mohamed Naim, Asmadi; Isa, Mohamad Yazid; Hamid, Mohd Liki (Emerald Group Publishing Limited, 2013)
Purpose– This paper aims to analyse the new standards on Sukuk which was issued by the Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) as a result of the strong critics posed by Shaykh Taqi in the end of 2007 that 85 percent of Sukuk issuance were not in line with the teachings of Shariah.Design/methodology/approach– This study reviewed samples of Sukuk prior and after the new AAOIFI pronouncement by focusing on controversial areas such as ownership transfer, pricing and guarantee element.This paper used content analysis approaches to analyse the pronouncement and the samples. Findings – The findings showed that there were negligible changes on the principle term and condition (PTC) of the Sukuk after the pronouncement, thus it did not have much effect in changing the Shariah Advisors and industry players when deciding more authentic principles and decisions.Originality/value – Based on the findings, it is acceptable that the advisors tried their very best in making efforts to minimize controversial decisions as to suit current financial practices.